How are the Performance of Small Businesses Influenced by HRM Practices and Governmental Support? - Yusra Yaseen, Lazim; Noor Azlinna, Azizan; Sorooshian, Shahryar (MCSER-Mediterranean Center of Social and Educational Research, 2015)

(untitled)
Human resources have been regarded as the most important asset for any organization because of its essential part in achieving the sustainable competitive advantage and survival. Managing human resources is very challenging and requires an effective bundle of practices that contribute to attaining the organizational goals. This study tries to confirm the importance of HRM practices in small businesses which came to play a vital role in the economies of the world, through clarifying the influence of HRM practices on the organizational performance, using a mediating variable (employees’ outcomes). Also the study attempts to highlight the key role of governmental support from view point of small businesses, through verifying the significant relationship between governmental support and the organizational performance. It was hypothesized that HRM practices will be positively related to the organizational performance (financial & operational), and that employees’ outcomes would serve as a mediator in the relationship between HRM practices and performance. Also it was hypothesized that the governmental support will be positively related to organizational performance. Structural Equation Modelling (SEM) with Amos has been applied in this research. The research sample consist (265) small manufacturing businesses in Malaysia. The statistical results showed significant relationships in direct and indirect models of study, and partially mediated in mediation models. © 2015 Mediterranean Journal of Social Sciences. All rights received.